Factors Associated With Medication Adherence In Elderly Retired Outpatients In São Paulo, Brazil - Valassi, Juliana Martins Ribeiro (Patient Prefer Adherence, 2019)
OBJECTIVE: To evaluate medication adherence and associated socioeconomic factors in elderly Brazilians. METHODOLOGY: This observational study was conducted with 159 elderly retired in an outpatient clinic in the city of São Paulo. Treatment adherence was assessed with the questions from the Morisky Green Levine Medication Adherence Questionnaire, and medications were classified using the Anatomical Therapeutic Chemical system. Statistical tests and adjusted Poisson regression models were used to analyze variables. RESULTS: The study population was mostly female (67.5%), had an average age of, and took an average of 6.5 medications per day. The most commonly used drugs were agents acting on the renin-angiotensin system (67.9%), statins (62.3%), antithrombotic agents (48.4%), and biguanides (37.1%) for the treatment of hypertension (76.7%), dyslipidemia (54.1%), and diabetes (47.8%). The rate of adherence was below 60% in the groups of participants that were analyzed except for the high household income category, which had a rate of 75.8%. CONCLUSION: Medication adherence among the elderly was low in all categories except for the high household income category, a relevant finding that will help to understand medication adherence patterns in elderly Brazilians.